National Economic Activities in the Past and In the Future - Martišius, Stanislovas Algimantas (Lithuanian Journal of Statistics, 2018)
[full article and abstract in Lithuanian; abstract in English]Lithuanian economy, over the last century, has been subject to significant changes and various vicissitudes. After restoring its independence (1918), Lithuania had to start everything from the very beginning, i.e. as soon as possible to commence the development of its own economy under challenging and complex political conditions. Small and medium-sized business, crafts, retail trade were the first significant changes. Unfortunately, Lithuania, at that time, was missing its own independent, entrepreneurial, life-innovation-sensitive entrepreneurs' layer. The foregoing was determined both by objective (the global economic crisis) and subjective (lack of working capital, negligible purchasing power, public institutions' red tape, etc.) reasons. The inter-war period was too short for Lithuania's economy to obtain the best possible results though certain conditions were ensured, and much solid work was done in the field of social policy. Current politicians and economists still have what to learn from that time political insight, economic rationality, legislative technique. Unfortunately, the Second World War and the subsequent authoritarian character of the Soviet Union's economy influenced the nature of Lithuania's economy, irrational attitude towards its changes taking place at that time. For very many, restoration of independence was unexpected. It was necessary to start managing Lithuanian economy in the absence of almost any practical, scientific expertise and input so that to begin objective and significant economic reforms. In order to focus on European management standards, Lithuania should substantially improve its management in all activity fields. Unfortunately, Lithuania's science is still lacking the applied research orientation, natural connection of theory and practice. Becoming a Member State of the European Union, we should manage to realize ourselves. Only universal prosperity, high level of cultural and well educated youth, as well as proper and sufficient understanding of democracy ideals will enable Lithuania to speed up its efforts and to become a full member of the free EU.Marginal efficiency theory, Keynesian view, neoclassical attitude towards economics, Monetarism, Neoliberalism and institutionalists' attitudes, hopefully, will promote the efforts to form a base of uniform researches, favorable for political scientists and economists. Creation of macroeconomics, undoubtedly, is a major achievement of the 20th Century economics. Nobel Prize Laureates: Milton Friedman, James Tobin, Franco Modigliani, Lawrence R. Klein, Robert M. Solow and other famous scientists are the most prominent contributors in this field. Regretfully, the reverse process still often happens on the Lithuanian revival path: fragmentation of social sciences, i.e. theoretical researches are prevailing over the empirical studies in the field of social sciences abroad. Lithuania, however, is still lacking the same. The number of successors of the interwar-period intellectuals (D. Cesevičius, D. Budrys, P. Padalskis and others) is alarmingly low. Current economists do not have enough consistency and are not well prepared from the theoretical point of view. In my opinion, teaching assignments of the mathematized economic theory for the 21st Century's future economists shall be notably reinforced and enhanced. Furthermore, they should be able themselves not only to interpret such theories, but also to create new ones. Full symbiosis of the economic theory and practice is of vital importance.
Keywords: Lithuanian economy; marginal efficiency theory; Keynesian concept; Neoclassical School; Monetarism; Neoliberalism; institutionalists; macroeconomic theory